Suspected or protected? Perceptions of procedural justice in ethnic minority youth's descriptions of police relations - Saarikkomäki, Elsa (Policing and society, 2021)
Research has highlighted the harmful effects of targeted police practices and the subsequent low trust in the police among ethnic minorities. However in spite of this research, there still exists a relative lack of knowledge on the day-to-day relations between ethnic minority youth and the police and on the perceptions that ethnic minorities have of procedural justice. Furthermore, comparative and cross-nation research is needed. This study, using data from 121 in-depth interviews, investigates how ethnic minority youth living in Finland, Denmark, Norway and Sweden describe policing practices. Our findings indicate that descriptions were quite similar in each of the four Nordic countries. While on the one hand, ethnic minority youth felt suspected by the police for no justifiable reason, thereby creating strong feelings of procedural injustice and unfairness, on the other hand, they described encounters, where they felt protected by the police and in general trusted the institution of the police. As such ambiguity has often been neglected, this article highlights the positive perceptions of the police but also argues that targeted police practices can undermine notions of procedural justice, trust in policing and a sense of belonging.